(3GdhLjR aj GdYbhO GdJLGQjI hGdYedjGJ GdeUQajI (B/s - (3OhjOGQ, gGfj eMeOs ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2003)
(3GdYbhO GdJLGQjI, GdHjY HGdJbSjW , GdhcGdI HGdYehdI, GdQgf GdJLGQj, fbd GdHVGFY, GdYedjGJ GdeUQajI,GdMSGHGJ GdeUQajI,YedjGJ GdEFJeGf GdeUQaj, GdYedjGJ GdhGQOI Ydi GdUchc GdJLGQjIs
Keywords: (3GdYbhO GdJLGQjIs; (3GdYedjGJ GdeUQajIs